2018
DOI: 10.1093/jas/skx017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of individual SCFA on the epithelial barrier of sheep rumen under physiological and acidotic luminal pH conditions

Abstract: The objective of this study was to investigate whether individual short-chain fatty acids (SCFA) have a different potential to either regulate the formation of the ruminal epithelial barrier (REB) at physiological pH or to damage the REB at acidotic ruminal pH. Ruminal epithelia of sheep were incubated in Ussing chambers on their mucosal side in buffered solutions (pH 6.1 or 5.1) containing no SCFA (control), 30 mM of either acetate, propionate or butyrate, or 100 mM acetate. Epithelial conductance (Gt), short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 62 publications
0
36
0
Order By: Relevance
“…Alterations in J fluor and G t are commonly used to assess the permeability of the paracellular space to large ( J fluor ) and small ions ( G t ), assuming that the transcellular route has negligible ( J fluor ) or rather constant ( G t ) contribution to these functional barrier readouts. Nevertheless, we have demonstrated in previous studies that fluorescein is also able to use the transcellular route for permeation across RE, for example, after an acid challenge (Greco et al, ; Meissner et al, ). Based on the fact that G t and the protein expression of all tested TJ proteins were unchanged by GLP‐1 and GLP‐2 in the present study, we thus propose that paracellular barrier function of RE was not affected by these hormones during the 7‐hr incubation, despite the fact that J fluor was changed in the last flux period by either of them.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Alterations in J fluor and G t are commonly used to assess the permeability of the paracellular space to large ( J fluor ) and small ions ( G t ), assuming that the transcellular route has negligible ( J fluor ) or rather constant ( G t ) contribution to these functional barrier readouts. Nevertheless, we have demonstrated in previous studies that fluorescein is also able to use the transcellular route for permeation across RE, for example, after an acid challenge (Greco et al, ; Meissner et al, ). Based on the fact that G t and the protein expression of all tested TJ proteins were unchanged by GLP‐1 and GLP‐2 in the present study, we thus propose that paracellular barrier function of RE was not affected by these hormones during the 7‐hr incubation, despite the fact that J fluor was changed in the last flux period by either of them.…”
Section: Discussionmentioning
confidence: 80%
“…The procedures for protein extraction and Western blot analysis of claudin-1, -4, -7 and occludin were performed as described previously (Greco et al, 2018), except that blotting was performed at 80 V for 60 min and that antibodies for the reference gene (anti-βactin) were diluted 1 in 2000. The zero hypothesis was considered disproved with p-values < .05.…”
Section: Protein Extraction and Western Blot Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…These data suggested that higher expression of IGFBP5 in rumen papillae is associated with the changes of the fermentation in rumen. Higher expression of IGFBP5 in rumen papillae might be necessary for adaptation to highly fermentable diet causing disruption of rumen epithelial barrier (Greco et al, 2018;Meissner et al, 2017;Steele et al, 2011). IGFBP5 induced monocyte migration in lung epithelium in mice (Yasuoka, Yamaguchi, & Feghali-Bostwick, 2009).…”
Section: Discussionmentioning
confidence: 99%